2017
DOI: 10.1001/jamapsychiatry.2016.3803
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glucose Homeostasis in First-Episode Schizophrenia

Abstract: These findings show that glucose homeostasis is altered from illness onset in schizophrenia, indicating that patients are at increased risk of diabetes as a result. This finding has implications for the monitoring and treatment choice for patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
203
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(227 citation statements)
references
References 68 publications
13
203
1
Order By: Relevance
“…While research regarding glucose metabolism in treatment-naïve, first episode patients with individual SMI suggest a pre-diabetic condition, we have limited knowledge on the differences of glucose metabolism across different diagnostic categories of SMIs. Therefore, the first aim of this study is to extend previous findings in patients with FEP (Greenhalgh et al, 2016;Perry et al, 2016;Pillinger et al, 2017) by conducting a systematic review and a meta-analysis of glucose intolerance in first episode, treatment-naïve patients with FEP, as well as first episode, treatment-naïve patients with depression and bipolar disorder. The second aim of this study is to compare the differences of pooled results from glucose metabolism outcomes between these diagnostic categories.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…While research regarding glucose metabolism in treatment-naïve, first episode patients with individual SMI suggest a pre-diabetic condition, we have limited knowledge on the differences of glucose metabolism across different diagnostic categories of SMIs. Therefore, the first aim of this study is to extend previous findings in patients with FEP (Greenhalgh et al, 2016;Perry et al, 2016;Pillinger et al, 2017) by conducting a systematic review and a meta-analysis of glucose intolerance in first episode, treatment-naïve patients with FEP, as well as first episode, treatment-naïve patients with depression and bipolar disorder. The second aim of this study is to compare the differences of pooled results from glucose metabolism outcomes between these diagnostic categories.…”
Section: Introductionmentioning
confidence: 95%
“…A recent Danish register study published in by Rajkumar et al reported 3.07 adjusted hazard ratio of diabetes diagnosis in treatment-naïve FEP patients compared to population sample, suggesting an increased endogenic risk for DM2 in FEP patients (Cohen & De Hert, 2011;Rajkumar et al, 2017). Three recent meta-analyses have shown significantly higher insulin resistance (IR), HbA1c, fasting insulin and glucose levels after oral glucose tolerance test (OGTT) in treatment-naïve, FEP compared to healthy controls (Greenhalgh et al, 2016;Perry et al, 2016;Pillinger et al, 2017). One of these meta-analyses (Greenhalgh et al, 2016) also showed higher fasting glucose levels in patients with FEP compared to healthy controls, whereas others reported no difference on fasting glucose levels between these two groups.…”
Section: Introductionmentioning
confidence: 99%
“…Although, certain antipsychotic medications (McEvoy et al, 2005; De Hert et al, 2006), illness chronicity, lifestyle habits such as diet, smoking, etc., and aging related factors (Subramaniam et al, 2003) contribute to incidence of metabolic syndrome; a higher prevalence of metabolic syndrome and type II diabetes during early stages of (Correll et al, 2014) and antipsychotic medication naïve (Ryan et al, 2003; Fernandez-Egea et al, 2009; Pillinger et al, 2017) schizophrenia patients has been reported. Besides the profound effects metabolic syndrome and type II diabetes have on premature mortality in schizophrenia, they have also been associated with poor school performance in adolescence (de Nijs and Pet, 2016), sensory gating deficits (Micoulaud-Franchi et al, 2015) and other neurocognitive outcomes (Lindenmayer et al, 2012; Goughari et al, 2015).…”
Section: Schizophrenia Metabolic Syndrome and Type II Diabetesmentioning
confidence: 99%
“…66 Poor physical health can be anticipated from early in the course of psychosis, when poor mental health, unhealthy lifestyle, and social disadvantage may combine with adverse treatment effects. For instance, meta-analytic evidence from 51 randomised controlled trials shows most antipsychotic induced weight gain occurs early in the disorder (see fig 3⇓), 67 impaired glucose tolerance may be evident even before starting antipsychotic medication, 68 while 59% of people presenting with first episode psychosis already smoke. 69 Because of the typically young age of onset, this puts people with psychosis at much higher risk of premature death from physical illness in their 20s or 30s, an age when primary care would not usually consider active primary or secondary prevention.…”
Section: Psychosis Physical Health and Primary Carementioning
confidence: 99%